Land‐use effects on the hyporheic ecology of five small streams near Hamilton, New Zealand - Andrew J. Boulton; Mike R. Scarsbrook; John M. Quinn; Greg P. Burrell (New Zealand Journal of Marine and Freshwater Research, 1997)
Although the importance of the subsurface saturated interstitial zone (hyporheic zone) to the ecological functioning and maintenance of water quality of stream ecosystems is well known, there is little information on the impacts of different forms of land use upon this zone. Hyporheic physico‐chemistry and invertebrates were compared among small streams draining hill‐country catchments under pasture, exotic pine forest, and native forest near Hamilton, New Zealand. In streams draining native forest, the hyporheic zone harboured a relatively diverse invertebrate fauna comprising mostly taxa common in the surface benthos, although a few apparently obligate hyporheic taxa (ostracods, blind amphipods) were collected. Few individuals and taxa occupied the hyporheic zones of streams draining pasture with some groups such as water mites conspicuously absent. The hyporheos of the stream in exotic pine forest was similar in richness and abundance to that of the pasture streams. Hyporheic water temperatures were significantly higher in the pasture streams than those in pine or native forest. There were strong positive correlations between percentage saturation of dissolved oxygen in the hyporheic zones of all streams and both species richness and total invertebrate abundance. We suggest that land clearance for pasture leads to hill slumping and siltation that bury the lateral bars along the stream channels, rendering this habitat unsuitable for hyporheic invertebrates. Channel narrowing and incision may physically remove further hyporheic habitat, and the reduction of flushing flows to remove interstitial silt and clay leads to low hyporheic dissolved oxygen concentrations and reduced colonisation by surface benthos.